Key Concepts in Theatre/Drama Education - Schonmann, Shifra; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
Key Concepts in Theatre Drama Education provides the first comprehensive survey of contemporary research trends in theatre/drama education. It is an intriguing rainbow of thought, celebrating a journey across three fields of scholarship: theatre, education and modes of knowing. Hitherto no other collection of key concepts has been published in theatre /drama education. Fifty seven entries, written by sixty scholars from across the world aim to convey the zeitgeist of the field. The book$1 (Bs key innovation lies in its method of writing, through collaborative networking, an open peer-review process, and meaning-making involving all contributors. Within the framework of key-concept entries, readers will find valuable judgments and the viewpoints of researchers from North and South America, Europe, Asia, Africa, New Zealand and Australia. The volume clearly shows that drama/theatre educators and researchers have created a language, with its own grammar and lucid syntax. The concepts outlined convey the current knowledge of scholars, highlighting what they consider significant. Entries cover interdependent topics on teaching and learning, aesthetics and ethics, curricula and history, culture and community, various populations and their needs, theatre for young people, digital technology, narrative and pedagogy, research methods, Shakespeare and Brecht, other various modes of theatre and the education of theatre teachers. It aims to serve as the standard reference book for theatre/drama education researchers, policymakers, practitioners and students around the world. A basic companion for researchers, students, and teachers, this sourcebook outlines the key concepts that make the field prominent in the sphere of Arts Education.s
Keywords: Education; Education; Arts Education